Cross-Border Multi-Jurisdictional Task Force Evaluation, San Diego and Imperial Counties, California, 2007-2012 - Burke, Cynthia ([Verlag nicht ermittelbar], 2016)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. The study involved a three-year evaluation of two efforts to target crime stemming from the Southern Border of the United States - one which funded greater participation by local officers on four FBI-led multi-jurisdictional task forces (MJTFs) and another that created a new multi-jurisdictional team. As part of this evaluation, researchers documented the level of inter-agency collaboration and communication when the project began, gathered information regarding the benefits and challenges of MJTF participation, measured the level of communication and collaboration, and tracked a variety of outcomes specific to the funded MJTFs, as well as three comparison MJTFs. Multiple methodologies were used to achieve these goals including surveys of task forces, law enforcement stakeholders, and community residents; law enforcement focus groups; program observations; and analysis of archival data related to staffing costs; task force activities; task force target criminal history; and prosecution outcomes. The study is comprised of several data files in SPSS format: Imperial County Law Enforcement Stakeholder Survey Data (35 cases and 199 variables) Imperial County Resident Survey (402 cases and 70 variables) Imperial Task Force Survey (6 cases and 84 variables) Prosecution Outcome Data (1,973 cases and 115 variables) San Diego County Resident Survey (402 cases and 69 variables) San Diego Law Enforcement Stakeholder Survey (460 cases and 353 variables) San Diego Task Force Survey (18 cases and 101 variables) Staff and Cost Measures Data (7 cases and 61 variables) Criminal Activity Data (110 cases and 50 variables) Additionally, Calls for Service Data, Countywide Arrest Data, and Data used for Social Network Analysis are available in Excel format.